Ethno-linguistic features of some common language units in Kazakh, Turkish and Persian languages - Шaдкaм З. (Journal of Oriental Studies, 2018)
The Great Silk Road was an important place in the world in terms of trade, transportation and cultural relations, until the advent of the rapid development of machinery, engineering and industry. Along with trade, there are also linguistic and cultural relations in the cities by the Silk Road. That is why the common cultural, linguistic, religious beliefs and religious values are peculiar for the people living on the Silk Road. In the article, we will undertake ethno-linguistic analysis of some common words and phrases in Kazakh, Turkish and Persian languages; try to illustrate their usage and place in the Kazakh culture; show by examples that these languages were interconnected and coexisted from ancient to modern times.